Understanding Material Allowance as a Systemic Issue in Garment Manufacturing: An Activity-on-Arrow Case Study - Elvi Armadani; Ragil Alghifari Sendin; Chindy Elsanna Revadi; Arieviana Ayu Laksmi; Alek Topan Lubis; Hilmana Radhia Putera (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The garment manufacturing industry is required to maintain high production efficiency while meeting strict buyer specifications, particularly in make-to-order export-oriented operations. One recurring challenge in garment production is material allowance, which refers to excess material usage beyond planned requirements and may increase production costs while reducing resource efficiency. This study aims to analyze production business processes and identify factors contributing to material allowance in the manufacturing of Tommy Hilfiger products at PT XYZ, an export-oriented garment company in Indonesia. This research adopts a descriptive qualitative approach by applying the Activity-on-Arrow (AOA) method to map activity sequences and interdepartmental relationships across the production workflow. Primary data were collected through direct observation and semi-structured interviews, while secondary data were obtained from internal company documents and material usage records. Quantitative analysis of raw material consumption was conducted across three production seasons—Fall 2021, Pre-Spring 2022, and Spring 2022. A fishbone diagram was used to analyze the root causes of material allowance. The results show that material allowance consistently occurred at approximately 2% across all observed production seasons. AOA-based analysis identifies cutting and sewing processes as critical stages where rework and quality deviations frequently arise. Human-related factors and method-related issues were found to be the primary contributors to material allowance. These findings highlight the importance of improving process coordination, quality control, and operator management to reduce material allowance and enhance production efficiency.